2019
DOI: 10.11648/j.sjcm.20190802.11
|View full text |Cite
|
Sign up to set email alerts
|

Implanon Discontinuation Rate and It's Associated Factors in Debre Tabor Town, North Central Ethiopia

Abstract: Family planning could avert a significant number of maternal mortality and contributes to child survival with its focus on women's rights. Generally, a long-acting reversible contraceptive is more effective and cover all the advantage and eliminates the disadvantages of other types of contraceptives. The acceptance and utilization of long-acting reversible contraceptive including implanon were very low in many developing countries including Ethiopia. The purpose of this study was to assess the level of discont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The publication year ranged from 2015 to 2021. The minimum and the maximum sample sizes were 132 and 711, which were obtained from studies conducted in Amhara 34 and South Nations, Nationalities, and Peoples’ Region (SNNPR), 36 respectively. Regarding the distribution of studies across the geographic region of the country, four were from the Amhara region, 28,34,35,37 three were from the Oromia region, 28,29,33 two were from Tigray, 32,38 and two were from SNNPR 31,36 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The publication year ranged from 2015 to 2021. The minimum and the maximum sample sizes were 132 and 711, which were obtained from studies conducted in Amhara 34 and South Nations, Nationalities, and Peoples’ Region (SNNPR), 36 respectively. Regarding the distribution of studies across the geographic region of the country, four were from the Amhara region, 28,34,35,37 three were from the Oromia region, 28,29,33 two were from Tigray, 32,38 and two were from SNNPR 31,36 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 11 cross-sectional studies were included in this systematic review and meta-analysis. [28][29][30][31][32][33][34][35][36][37][38] A total of 4320 Implanon users were considered in the meta-analysis. In all of the studies, data were collected by a face-to-face interview using a pre-tested, interviewer-administered questionnaire.…”
Section: Characteristics Of Identified Studiesmentioning
confidence: 99%
“…All studies included in this meta-analysis were published between 2015 and 2022. A total of 5012 women who were using contraceptive implants were participated in the analysis, with a minimum sample size of 134 16 and maximum of 711. 17 From 13 articles included in this systematic review and meta-analysis, only four regions of Ethiopia were identified.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…17 From 13 articles included in this systematic review and meta-analysis, only four regions of Ethiopia were identified. Of the total studies included, four were conducted in Amhara; 16,[18][19][20] four in South Nations Nationalities and Peoples of Ethiopia national (SNNPR), 17,[21][22][23] three studies in Oromia [24][25][26] and two in Tigray. 27,28 Six studies were conducted in urban areas and the rest seven were conducted in rural areas.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation